Value of T2 Mapping MRI for Prostate Cancer Detection and Classification. Issue 2 (11th July 2022) - Klingebiel, Maximilian; Schimmöller, Lars; Weiland, Elisabeth; Franiel, Tobias; Jannusch, Kai; Kirchner, Julian; Hilbert, Tom; Strecker, Ralph; Arsov, Christian; Wittsack, Hans‐Jörg; Albers, Peter; Antoch, Gerald; et al.
Abstract : ROI Measurements of benign tissue in the peripheral zone (PZ; purple ROI) and transition zone (TZ; orange ROI), and PCA (red ROI). Quantitative T2 map (A), T2 TSE (B), and calculatedadc map of RS‐DWI (C). On Radical prostatectomy (RPE), an ISUP grade 5 PCA was confirmed. by Maximilian Klingebiel et al. (413–422)